PARTISIPASI WANITA DALAM REHABILITASI HUTAN MANGROVE DI DESA INALATAN KECAMATAN BONUBOGU KABUPATEN BUOL - Djabar, Murni (Universitas Gorontalo, 2018)
Coastal women, especially housewives generally in Indonesia, including in the district of Buol has a very big role in the activities of earning a living for his family. The participation of coastal women in mangrove forest rehabilitation activities is an effort to empower coastal women to become one of the driving forces of successful mangrove forest rehabilitation. This research aims to examine the participation of Coastal Women in supporting Mangrove forest rehabilitation in Inalatan Village Bunobogu District Buol Regency viewed from the aspect of community understanding about rehabilitation mangrove forest and the form of participation or community participation in mangrove forest rehabilitation activities. The community participation studied in this research is related to individual community participation in mangrove forest rehabilitation activities, the target of the community taken in this research is from 30 female respondents through questionnaire interview technique. This research was conducted in coastal area of Inaktif Village Bunobogu District Buol Regency for 2 months tehitung from January until February 2018. The method of analysis used in this research is using qualitative descriptive analysis method.The results of this study can be seen based on the daily activities of the community in the household for 24 hours, the understanding of the women community on the rehabilitation activities, the participation of women in planning activities, implementation activities and evaluation activities of reforestation of mangrove forests, the fifth form of community participation in this research is including in the category of high forms of community participation because all forms of partipasi exceeds the average percentage above 50%